Women's Participation In Bumdes Management In Tumalehu Barat Village, Manipa Islands Sub-District - Hamdan Salisi; Aphrodite M. Sahusilawane; Junianita F. Sopamena (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to find out how women participate and what factors influence women in managing BUMDes in Tumalehu Barat Village, Manipa Islands District. The sample used in this study is a saturated or census sampling technique. With a total sample of 23 people. The results of the study showed that women's participation in the management of BUMDes Kapitan Yongker was very good, in terms of the activities carried out in the planning process, implementation of activities, deliberations and expression of opinions, and utilization of the results. This is supported by several driving factors such as self-will, ability and expertise, BUMDes ADRT, and sufficient natural resources. However, there are still obstacles in its management, namely the dual role of women, the timing of BUMDes management, the distribution of processed BUMDes products, the lack of market availability to sell every BUMDes product, there is no permanent courier who can deliver processed BUMDes products when there are orders from outside the island. Manipa.